PENGUKURAN EFISIENSI PENERAPAN KNOWLEDGE MANAGEMENT (KM) MELALUI SECI MODEL PADA PT ASURANSI MSIG INDONESIA - Lathifah, Fitriana -; Kartika, Lindawati - (Politeknik Negeri Semarang, 2016)
PT Asuransi MSIG Indonesia has beenapplying some criteria of the KM. However,the company have not manage and exploit itin such a way yet. The purposes of thisresearch are (1)to know the implementationof the KM in PT Asuransi MSIG Indonesiaand (2)to measure how large the efficiency ofthe KM which is already running. Thetechniques of data collection arequestionnaire and literature study. DataEnvelopment Analysis (DEA) and descriptiveanalysis are used as methods in this study.The result of the study showed that (1)theprocess of the KM which is implemented canbe classified into 4 knowledge conversionmodel SECI (Socialization, Externalization,Combination, Internalization) and most ofthem are belong to socialization process.(2)The results of the measurements using theDEA showed that 9 departments of 12departments of PT Asuransi MSIG Indonesiahave been applying the KM efficiently and therest, 3 of departments have not being efficientyet, i.e. Claim Business, Brokerage Businessand IT&OPTIMUS. Therefore, needs toformalize the application of the KM system onPT Asuransi MSIG Indonesia throughapplication of Community of Practice System.